The relation of serum anti-(GalNAc beta) and -para — forssman disaccharide IgG levels to the progression and histological grading of gastrointestinal cancer - Smorodin, E.P.; Kurtenkov, O.A.; Sergeyev, B.L.; Chuzmarov, V.I.; Afanasyev, V.P. (Experimental Oncology, 2007)
Earlier we found two unusual IgG-antibody specificities to GalNAc? and GalNAcβ1-3GalNAcβ (Para — Forssman disaccharide, PFdi) carbohydrate ligands in human serum. The aim of the study was to evaluate whether elevated antibody levels are related to the progression of gastrointestinal cancer and the histopathological grading. Methods: Specific IgG levels were tested in 159 patients with gastric cancer, 88 patients with colorectal cancer and 96 blood donors by the ELISA using synthetic polyacrylamide (PAA) conjugates, GalNAcβ-PAA and PFdi-PAA. Biochemical and haematological analyses were performed using automatic equipment. Results: The anti-PFdi IgG levels were significantly higher in patients with gastric and colorectal cancer than in donors: in stages II–IV, P = 0.0002 – 0.04 (U-test). The elevated anti-PFdi IgG level was associated with the advanced gastric cancer: in stages II, III, IV vs stage I (P = 0.004 – 0.06) and in case of the tumor size T2 + T3 vs T1 (stages I, II; P = 0.03). Differences in anti-GalNAcβ IgG level were insignificant. No relation between antibody levels and the regional and distant metastases of gastric or colorectal cancer was found. The lower anti-GalNAcβ IgG level was associated with lower-differentiated carcinomas (P = 0.01 – 0.04). Prolonged postoperative changes in the levels of both antibodies during the follow-up were established. An elevation of both antibody levels in patients with gastrointestinal cancer was revealed after a surgical removal of G3-tumors (P = 0.003 – 0.01). The anti-PFdi IgG levels correlated with the levels of the C-reactive protein: r = 0.50, P = 0.003. The anti-GalNAcβ IgG levels correlated with the percentage of peripheral blood monocytes: r = 0.42, P = 0.002. Conclusion: The association of the anti-PFdi IgG level with cancer progression suggests the implication of antibodies in the pathogenesis of gastrointestinal cancer. Further studies are required to identify natural targets of antibodies, their relation to other diseases, prognostic significance in cancer. В сыворотке крови человека ранее выявлены IgG-антитела к углеводородным лигандам GalNAcβ и GalNAcβ1-3GalNAcβ
(дисахарид Пара — Форсманна, PFdi). Цель исследования — выяснение связи повышенного уровня антител с прогрессией
и гистологическими особенностями опухолей желудочно-кишечного тракта. Методы: обследовали 159 больных раком
желудка, 88 — раком кишечника и 96 здоровых людей — доноров крови. Уровень специфических IgG-антител определяли
методом ИФА с использованием синтетических конъюгатов полиакриламида (ПАА), GalNAcβ-ПАА и PFdi-ПАА. Уделение
биохимических и гематологических показателей проводили с использованием автоматических анализаторов. Результаты:
уровень анти-PFdi IgG у пациентов со злокачественными новообразованиями в стадиях II–IV (P = 0,0002 – 0,04) достоверно
выше, чем у доноров. Повышенный уро вень анти-PFdi IgG ассоциировался с прогрессией рака желудка (в стадиях II–IV по
сравнению со стадией I P = 0,004 – 0,06) и увеличением размера опухоли (T2 + T3 по сравнению с T1, стадии I, II; P = 0.03).
Различия в уровнях анти- β IgG незначительные. Не выявлено взаимосвязи между уровнем антител и метастазированием
опухолей желудка и кишечника. Более низкий уровень анти- β IgG определяли у больных с менее дифференцированными
опухолями (P = 0,01 – 0,04). В период послеоперационного наблюдения отмечали изменения уровня обоих
типов антител. После хирургического удаления опухолей органов желудочно-кишечного тракта (стадия дифференцировки
G3) повышался уровень как анти-PFdi IgG, так и анти- βIgG (P = 0,003 – 0,01). Уровень анти-PFdi IgG коррелировал
с уровнем С-реактивного белка (r = 0,50, P = 0,003), а уровень анти-GalNAcβ IgG — с относительным количеством моноцитов
в периферической крови (r = 0,42, P = 0,002). Выводы: установлена зависимость уровня анти-PFdi IgG от опухолевой
прогрессии, что подтверждает их участие в патогенезе злокачественных новообразований органов желудочно-кишечного
тракта. Необходимы дальнейшие исследования по определению природных мишеней для антител, роли в развитии других
заболеваний и прогностическом значении при онкологической патологии.